Impact of foreign exchange exposure and shariah-compliant status on Malaysian firms’ hedging practice - Adilah A. Wahab,; Ruzita Abdul-Rahim,; Hawati Janor, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study investigates the impact of foreign exchange (forex) exposure and Shariah-compliant status on firms’ decision to practise hedging. It employs panel multiple and multinomial logistic regression on 702 firm-year observations from 117 non-financial listed firms over the period from 2010 to 2015. The sample consists of 70% Shariah-compliant firms, representative of the 74%-85% Shariah-compliant firms listed on Bursa Malaysia during the study period. From the multinomial logistic regression, this study finds total and net foreign currency exposures are significant in predicting hedging for firms that practice one and two hedging instruments. Moreover, the results also reveal that Shariah-compliant status always significantly and directly influence firms that hedge, except for firms that use four hedging instruments. This study contributes to the literature by introducing direct measurements of foreign currency exposure which prove to be significant indicators of forex exposure. Accurate measurement of forex exposure is crucial as it has implications on the firms’ ability to predict its cash flows, commit to future projects, and subsequently, increase its value. Since firms do not disclose whether the instruments used are conventional or Shariah-compliant, this study assumes that all instruments are conventional and therefore, being Shariah-compliant hinder the firms from practising hedging. However, the results reveal those firms that hedge are indeed Shariah-compliant. This finding should raise a great concern among the Islamic capital market regulators to require stricter rules and greater transparency among Shariah-compliant firms.